ByzRev 01.2019.001: Michael Angold, Nicholas Mesarites: His life and works (in translation) - Dimitriadis, Stefanos (The Byzantine Review, 2019)
Nicholas Mesarites. His life and works (in translation). Translated with notes and commentary by Michael Angold (Translated Texts for Byzantinists 4). Liverpool: Liverpool University Press 2017. 374 pp. ISBN: 9781786940063 (Hardback £85.00)